The Relative Orientation of the Trunk and Tibia can be Used to Estimate the Demands on the Hip and Knee Extensors During the Barbell Back Squat - Barrack, A. J.; Straub, R. K.; Cannon, J.; Powers, C. M. (International Journal of Sports Science & Coaching, 2021)
Sagittal plane inclination of the trunk and tibia have been shown to independently modulate hip and knee extensor moments during squatting. The purpose of this study was to determine if the difference between sagittal plane trunk and tibia inclinations can be used to approximate the relative demand of the hip and knee extensors across a range of squatting conditions. Kinematic and kinetic data were obtained from 16 participants during 8 squat conditions in which trunk and tibia inclination were manipulated. The average hip/knee extensor moment ratio (HKR) was calculated during the lowering (eccentric) phase of each squat condition using inverse dynamics equations. Linear regression evaluated the association between the difference in trunk and tibia inclination at peak knee flexion and the average HKR. Across all squat conditions, the difference between trunk and tibia inclinations explained 70% of the variance in the average HKR (p < 0.001). The squat was knee extensor biased (HKR = 1.0) when the tibia was at least 8 degrees more inclined than the trunk. The results of this study indicate that the relationship between sagittal plane trunk and tibia inclination can be used to estimate the relative demand of the hip and knee extensors.